ULASAN PENERAPAN TEKNOLOGI PENANGGULANGAN BENCANA LAUT DI INDONESIA - Sriwanti Sriwanti; Muhammad Fakhri Ardyansyah (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Indonesia is a country prone to various types of marine disasters, such as tsunamis, earthquakes and volcanic eruptions. To mitigate the impact of these disasters, the development and application of technology in disaster management is very important. This review focuses on the technologies used in marine disaster mitigation in Indonesia. One of the key technologies used in disaster management is the Early Warning System (EWS). An EWS is a system that detects and notifies authorities and communities of an impending disaster, allowing them to take immediate action to minimize its impact. In Indonesia, EWS has been implemented to provide early warning against tsunamis, allowing people to evacuate to safer areas. This technology relies on a network of sensors installed in strategic locations, which monitor seismic activity and transmit real-time data to a central command center for analysis and dissemination of warnings. Another technology that has been utilized in disaster management is remote sensing. Remote sensing uses satellites and other airborne sensors to collect data about the Earth's surface, including ocean conditions and weather patterns. This data is then analyzed to provide information on potential disasters and their impacts. In Indonesia, remote sensing is used to monitor ocean conditions, such as sea surface temperature and wave height, to provide early warning of potential tsunamis, storms or other ocean-related disasters. Keywords : Disaster, Mitigation, Technology